Alumina-based adsorption material as well as preparation method and application thereof
By preparing aluminum oxide-based adsorption materials, and using materials such as metal salts and organic ligands to optimize the pore structure and chemical composition of the materials, the existing adsorbents have been solved, and the high adsorption amount, good selectivity and water resistance are achieved, which is suitable for carbon dioxide capture and purification.
Patent Information
- Application Number
- CN202510053719.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing carbon dioxide adsorbents have problems such as poor selectivity, poor water resistance, and low total adsorption, which limits their use in large-scale applications.
By preparing aluminum oxide-based adsorption materials, the pore structure and chemical composition of the material are optimized by materials such as metal salts and organic ligands, their adsorption capacity and selectivity to carbon dioxide are improved, and the stability of the material is improved through high-temperature calcination and alternating pH control processes such as process methods.
It has achieved high adsorption, good selectivity and water resistance, high structural strength of the material and good thermodynamic stability, suitable for carbon dioxide capture and purification, and has large-scale application value.
Smart Images

Figure CN119746804A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adsorption materials, and in particular to an alumina-based adsorption material and a preparation method and application thereof. Background Art
[0002] In recent years, with the increasing attention paid to global climate change at home and abroad, environmental pollution control and energy crisis have gradually become major issues that urgently need to be addressed at home and abroad. Researchers have paid more and more attention to the emission control of industrial exhaust, especially greenhouse gases such as carbon dioxide.
[0003] CCUS (carbon capture, utilization and storage) is an important way to build green and clean energy. Among them, the adsorption method is regarded as one of the main research directions of CCUS technology due to its advantages such as low bed pressure, weak corrosiveness and simple regeneration operation.
[0004] At present, silica gel, molecular sieves, metal organic frameworks and activated carbon are the main adsorbent matrices for the physical adsorption of carbon dioxide. However, the existing adsorbents generally have problems such as poor selectivity, poor water resistance, and low total adsorption. For example, patent CN202380016229.1 develops silky zeolite with a MOR topological structure for removing CO2 from low CO2 content feed streams (including air). It can capture 1.15 mmolCO2 / g adsorbent from air with a carbon dioxide content of 400 ppm. However, the structural stability of zeolite materials is poor, especially when the water vapor content in the air is high, it will adsorb water. Zeolite materials are easily softened when exposed to water, which hinders the large-scale application of such adsorbents. Summary of the invention
[0005] The purpose of this application is to provide an alumina-based adsorption material and a preparation method thereof, wherein the product adsorption material can be applied to carbon dioxide capture and purification. The product adsorption material has high strength, stable structure, good water resistance, and excellent carbon dioxide adsorption effect, large adsorption capacity, and is conducive to large-scale application.
[0006] The technical solution of this application is as follows:
[0007] On the one hand, the present application provides an alumina-based adsorption material, which is prepared from raw materials including the following components:
[0008] Precursors, metal salts, organic ligands, organic solvents and water;
[0009] Wherein, the above-mentioned metal salt is at least one of a metal zirconium salt and a metal magnesium salt;
[0010] The above-mentioned precursor is prepared from the following components:
[0011] Sodium aluminate solution, ethanolamine solution and oxalic acid solution;
[0012] Wherein, the above-mentioned ethanolamine solution is diethanolamine or triethanolamine.
[0013] Furthermore, in some embodiments of the present application, the mass ratio of the precursor, metal salt, organic ligand, organic solvent and water in the above raw materials is 100:(1-5):(1-10):(1-10):(5-20).
[0014] In the above embodiments, by precisely controlling the composition ratio of the components, the composition and structure of the adsorption material can be optimized so that the adsorption performance can reach the best state.
[0015] Furthermore, in some embodiments of the present application, the organic ligand is triethylenediamine or triethylenetriamine.
[0016] Furthermore, in some embodiments of the present application, the organic solvent is tetrahydrofuran or acetone.
[0017] Furthermore, in some embodiments of the present application, the mass concentration of the ethanolamine solution is 2-10%, and the mass concentration of the oxalic acid solution is 1-10%.
[0018] The present application also provides a method for preparing the above-mentioned alumina-based adsorption material, which comprises the following steps:
[0019] Preparation of precursor: Alternately add ethanolamine solution and oxalic acid solution to sodium aluminate solution to react to obtain colloidal material, and then wash, dry, grind, and calcine to obtain the precursor;
[0020] Preparation of adsorption material: Precursor, metal salt, organic ligand, organic solvent and water are taken, mixed and sealed in a container, then heated to react to obtain a mother liquor, and then the mother liquor is evaporated and dried to obtain a finished adsorption material.
[0021] In the above embodiment, the process improves the structural strength, stability and other properties of the product adsorbent by preparing a macroporous alumina precursor material with steam stability as the matrix of the product adsorbent; at the same time, its alumina matrix has a larger pore size, which is beneficial to increase the specific surface area and porosity of the adsorbent material, thereby enhancing its adsorption capacity.
[0022] During its preparation process, the pH of the system is controlled by alternately adding ethanolamine solution and oxalic acid solution, which ensures the stability and consistency of the reaction conditions and helps to form a uniform pore structure. By introducing metal salts, the chemical properties of the adsorbent material can be improved and its selective adsorption capacity for specific gases (such as carbon dioxide) can be increased; in particular, the selection of zirconium salts and magnesium salts can be optimized according to specific application requirements. The addition of organic ligands such as triethylenediamine and triethylenetriamine can adjust the surface properties of the adsorbent material and increase its interaction with the target gas, thereby enhancing the adsorption effect. The use of tetrahydrofuran or acetone as an organic solvent can effectively dissolve metal salts and organic ligands and promote their uniform distribution in the adsorbent material, thereby improving the uniformity and stability of the material.
[0023] The adsorption capacity can be further improved by adding organic ligands, metal salts and other materials; the pore distribution and specific surface area of the adsorption material can be adjusted and optimized by combining the methods of alternating pH control and sealing reaction in the preparation process. Ultimately, an adsorption material with high adsorption capacity, good water resistance, high structural strength and good thermodynamic stability can be obtained. This material can be effectively used in carbon dioxide capture and purification, has high economic benefits and is worth large-scale application.
[0024] Furthermore, in some embodiments of the present application, during the process of alternating addition of ethanolamine solution and oxalic acid solution, the pH of the system is adjusted to 9.0 when the ethanolamine solution is first added, and the pH of the system is adjusted to 6.0 when the oxalic acid solution is first added; diethanolamine and oxalic acid are repeatedly added alternately 3 to 5 times, and the pH of the system is finally controlled to 7.0.
[0025] Furthermore, in some embodiments of the present application, in the above-mentioned precursor preparation step, the gelling reaction temperature is 25-40°C.
[0026] Furthermore, in some embodiments of the present application, in the above-mentioned precursor preparation step, the calcination temperature is ≥500°C.
[0027] In the above embodiments, organic impurities in the precursor material can be removed by calcining at high temperature (≥500° C.), which is beneficial to further improve the thermal stability and mechanical strength of the product adsorption material.
[0028] Furthermore, in some embodiments of the present application, in the above-mentioned adsorption material preparation step, the reaction is heated at 40-60° C. for 12-48 hours to obtain a mother liquor; and the mother liquor is evaporated and dried at 100-180° C. to obtain the adsorption material.
[0029] On the other hand, an embodiment of the present application also provides an application of the above-mentioned alumina-based adsorption material in the capture and purification of carbon dioxide.
[0030] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0031] In view of the above aspects, the embodiments of the present application provide an alumina-based adsorption material and a preparation method thereof, as well as the application of the adsorption material in carbon dioxide capture and purification. The beneficial effects are as follows:
[0032] 1. High adsorption capacity: The adsorption capacity of carbon dioxide is improved by optimizing the pore structure and chemical composition of the material.
[0033] 2. Good selectivity: The introduction of metal salts and organic ligands enhances the selective adsorption of carbon dioxide and reduces the interference of other gases.
[0034] 3. Stable performance: Calcination treatment and reasonable proportioning make the adsorption material have good thermal stability and mechanical strength, suitable for long-term use. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 A schematic flow chart of a method for preparing an alumina-based adsorption material provided in an embodiment of the present application. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0038] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "includes..." do not exclude the existence of other identical elements in the process, method, article or device including its elements.
[0039] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.
[0040] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0041] Example 1
[0042] This embodiment provides an alumina-based adsorption material, and the preparation method thereof is as follows: Figure 1 As shown, the specific steps are as follows:
[0043] Precursor preparation: Alternately add a 10% diethanolamine solution and a 10% oxalic acid solution to a sodium aluminate solution [NaOH / Al(OH)3 molar ratio is 1.3, Al2O3 concentration is 10 g / L]; during the process of alternately adding the two solutions, adjust the system pH to 9.0 when the ethanolamine solution is first added, and adjust the system pH to 6.0 when the oxalic acid solution is first added; repeatedly add diethanolamine and oxalic acid alternately 3 times, and finally control the system pH to 7.0;
[0044] During the process, the system temperature was controlled at 40°C (i.e., the gelling reaction temperature), and the colloidal material was obtained by reaction. It was then washed with deionized water and filtered, dried in a 105°C forced air drying oven for 4 hours, ground into powder, and calcined in a 500°C muffle furnace for 4 hours to obtain a macroporous alumina precursor.
[0045] Preparation of adsorption material: Take the precursor, zirconium bromide, triethylenediamine, acetone and deionized water in a mass ratio of 100:1:1:1:5, place them in a container, mix them and seal them, then heat them in a water bath to 40°C and react for 48 hours to obtain a mother liquor, then place the mother liquor in a rotary evaporator and evaporate and dry it at 100°C to obtain a finished adsorption material.
[0046] Example 2
[0047] This embodiment provides an alumina-based adsorption material, and the preparation method thereof is as follows: Figure 1 As shown, the specific steps are as follows:
[0048] Precursor preparation: Alternately add a 2% triethanolamine solution and a 1% oxalic acid solution to a sodium aluminate solution [NaOH / Al(OH)3 molar ratio of 1.3, Al2O3 concentration of 10 g / L]; during the process of alternately adding the two solutions, adjust the system pH to 9.0 when the ethanolamine solution is first added, and adjust the system pH to 6.0 when the oxalic acid solution is first added; repeatedly add diethanolamine and oxalic acid alternately 3 times, and finally control the system pH to 7.0;
[0049] During the process, the system temperature was controlled at 25°C (i.e., the gelling reaction temperature), and the colloidal material was obtained by reaction. It was then washed with deionized water and filtered, dried in a 105°C forced air drying oven for 4 hours, ground into powder, and calcined in a 500°C muffle furnace for 4 hours to obtain a macroporous alumina precursor.
[0050] Preparation of adsorption material: Take the precursor, zirconium chloride, triethylenetriamine, tetrahydrofuran and deionized water in a mass ratio of 100:2:2:3:10, place them in a container, mix them and seal them, then heat them in a water bath to 60°C and react for 12 hours to obtain a mother liquor, then place the mother liquor in a rotary evaporator and evaporate and dry it at 150°C to obtain a finished adsorption material.
[0051] Example 3
[0052] This embodiment provides an alumina-based adsorption material, and the preparation method thereof is as follows: Figure 1 As shown, the specific steps are as follows:
[0053] Precursor preparation: Alternately add a 5% triethanolamine solution and a 6% oxalic acid solution to a sodium aluminate solution [NaOH / Al(OH)3 molar ratio of 1.3, Al2O3 concentration of 10 g / L]; during the process of alternately adding the two solutions, adjust the system pH to 9.0 when the ethanolamine solution is first added, and adjust the system pH to 6.0 when the oxalic acid solution is first added; repeatedly add diethanolamine and oxalic acid alternately 5 times, and finally control the system pH to 7.0;
[0054] During the process, the system temperature was controlled at 30°C (i.e., the gelling reaction temperature), and the colloidal material was obtained by reaction. It was then washed with deionized water and filtered, dried in a 105°C forced air drying oven for 4 hours, ground into powder, and calcined in a 500°C muffle furnace for 4 hours to obtain a macroporous alumina precursor.
[0055] Preparation of adsorption material: Take the precursor, zirconium chloride, magnesium nitrate, triethylenetriamine, tetrahydrofuran and deionized water in a mass ratio of 100:1:2:10:3:20, place them in a container, mix and seal, then heat to 60°C in a water bath and react for 24 hours to obtain a mother liquor, then place the mother liquor in a rotary evaporator and evaporate and dry it at 120°C to obtain a finished adsorption material.
[0056] Example 4
[0057] This embodiment provides an alumina-based adsorption material, and the preparation method thereof is as follows: Figure 1 As shown, the specific steps are as follows:
[0058] Precursor preparation: Alternately add a 10% triethanolamine solution and an 8% oxalic acid solution to a sodium aluminate solution [NaOH / Al(OH)3 molar ratio of 1.3, Al2O3 concentration of 10 g / L]; during the process of alternately adding the two solutions, adjust the system pH to 9.0 when the ethanolamine solution is first added, and adjust the system pH to 6.0 when the oxalic acid solution is first added; repeatedly add diethanolamine and oxalic acid alternately 4 times, and finally control the system pH to 7.0;
[0059] During the process, the system temperature was controlled at 35°C (i.e., the gelling reaction temperature), and the colloidal material was obtained by reaction. It was then washed with deionized water and filtered, dried in a 105°C forced air drying oven for 4 hours, ground into powder, and calcined in a 500°C muffle furnace for 4 hours to obtain a macroporous alumina precursor.
[0060] Preparation of adsorption material: Take the precursor, magnesium chloride, triethylenetriamine, acetone and deionized water in a mass ratio of 100:5:10:10:20, place them in a container, mix them and seal them, then heat them in a water bath to 60°C and react for 24 hours to obtain a mother liquor, then place the mother liquor in a rotary evaporator and evaporate and dry it at 180°C to obtain a finished adsorption material.
[0061] Example 5
[0062] This embodiment provides an alumina-based adsorption material, and the preparation method thereof is as follows: Figure 1 As shown, the specific steps are as follows:
[0063] Precursor preparation: Alternately add a 4% triethanolamine solution and a 3% oxalic acid solution to a sodium aluminate solution [NaOH / Al(OH)3 molar ratio is 1.3, Al2O3 concentration is 10 g / L]; during the process of alternately adding the two solutions, adjust the system pH to 9.0 when the ethanolamine solution is first added, and adjust the system pH to 6.0 when the oxalic acid solution is first added; repeatedly add diethanolamine and oxalic acid alternately 3 times, and finally control the system pH to 7.0;
[0064] During the process, the system temperature was controlled at 25°C (i.e., the gelling reaction temperature), and the colloidal material was obtained by reaction. It was then washed with deionized water and filtered, dried in a 105°C forced air drying oven for 4 hours, ground into powder, and calcined in a 500°C muffle furnace for 4 hours to obtain a macroporous alumina precursor.
[0065] Preparation of adsorption material: Take the precursor, zirconium chloride, magnesium nitrate, triethylenetriamine, tetrahydrofuran and deionized water in a mass ratio of 100:2:1:8:8:10, place them in a container, mix and seal, then heat to 50°C in a water bath and react for 24 hours to obtain a mother liquor, then place the mother liquor in a rotary evaporator and evaporate and dry it at 130°C to obtain a finished adsorption material.
[0066] Comparative Example 1
[0067] This comparative example provides an alumina-based adsorption material, which is prepared by the following method:
[0068] Take γ-alumina, zirconium chloride, triethylenetriamine, tetrahydrofuran and deionized water in a mass ratio of 100:2:10:3:20, put them in a container, mix them and seal them, then heat them in a water bath to 60°C and react for 24 hours to obtain a mother liquor, then put the mother liquor in a rotary evaporator and evaporate and dry it at 120°C to obtain a finished adsorption material.
[0069] Comparative Example 2
[0070] This comparative example provides an alumina-based adsorption material, which is prepared by the following method:
[0071] Alternately add a 10% diethanolamine solution and a 10% oxalic acid solution to a sodium aluminate solution [NaOH / Al(OH)3 molar ratio is 1.3, Al2O3 concentration is 10 g / L]; during the process of alternately adding the two solutions, adjust the system pH to 9.0 when the ethanolamine solution is first added, and adjust the system pH to 6.0 when the oxalic acid solution is first added; repeatedly add diethanolamine and oxalic acid alternately 3 times, and finally control the system pH to 7.0;
[0072] During the process, the system temperature was controlled at 40°C (i.e., the gelling reaction temperature), and the colloidal material was obtained by reaction. It was then washed with deionized water and filtered, dried in a 105°C forced air drying oven for 4 hours, ground into powder, and calcined in a 500°C muffle furnace for 4 hours to obtain the product adsorption material.
[0073] Test example
[0074] The adsorbent material samples obtained in Examples 1 to 5 and Comparative Examples 1 to 2 were ground and crushed, and then extruded into strips (diameter ~3 mm). A tubular reactor was used to load 20 g of the adsorbent material. The adsorbed gas was 12% carbon dioxide (volume content, the rest was nitrogen). Nitrogen was first introduced into the reaction tube and dried at 100° C. for 0.5 h. Then, adsorption was carried out under normal pressure, temperature of 75° C., and a flow rate of 30 mL / min of the mixed gas. After saturation, specific adsorption capacity data was obtained after chromatographic analysis.
[0075] The process parameters of Examples 1 to 5 are compared as shown in Table 1:
[0076] Table 1
[0077]
[0078] The chromatographic analysis results are shown in Table 2.
[0079] Table 2
[0080]
[0081] According to the same adsorption test method, the adsorption material obtained in Example 5 was subjected to adsorption operation and cyclic adsorption was performed 10 times. The adsorption capacity data obtained are shown in Table 3.
[0082] Table 3
[0083]
[0084]
[0085] According to the same adsorption test method, the adsorbent material of Example 5 was used, and the adsorbed gas with a carbon dioxide content of 12% (volume content, the rest is nitrogen) was replaced with a mixed gas with a carbon dioxide content of 300 ppm (i.e., ordinary air) as the adsorbed gas for testing. The adsorption capacity data obtained are shown in Table 4.
[0086] Table 4
[0087]
[0088] In addition, the specific surface area and pore size physicochemical properties of the adsorption materials of Examples 3 to 4 were characterized by low-temperature nitrogen adsorption. The results are shown in Table 5.
[0089] Table 5
[0090]
[0091] It can be seen from the results that the alumina-based adsorption material provided in the examples of the present application has good adsorption performance and excellent physical and chemical properties.
[0092] In summary, the embodiments of the present application provide an alumina-based adsorbent material, a preparation method and application thereof, and the application of the adsorbent material in carbon dioxide capture and purification. It improves the structural strength and stability of the product adsorbent by preparing a macroporous alumina precursor material with steam stability as the matrix of the product adsorbent, and further improves the adsorption capacity by adding organic ligands, metal salts and other materials; combined with the methods of alternating control of pH and sealing reaction in its preparation process, the pore distribution and specific surface area of the adsorbent material are adjusted and optimized, and finally a kind of adsorbent material with high adsorption capacity, good water resistance, high structural strength and good thermodynamic stability can be obtained, which can be effectively used in carbon dioxide capture and purification, with high economic benefits and large-scale application value.
[0093] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. An alumina-based adsorption material, characterized in that: It is prepared from raw materials including the following components: Precursors, metal salts, organic ligands, organic solvents and water; Wherein, the metal salt is at least one of a metal zirconium salt and a metal magnesium salt; The precursor is prepared from the following components: Sodium aluminate solution, ethanolamine solution and oxalic acid solution; Wherein, the ethanolamine solution is a diethanolamine solution or a triethanolamine solution.
2. The alumina-based adsorption material according to claim 1, characterized in that: The mass ratio of the precursor, the metal salt, the organic ligand, the organic solvent and the water in the raw material is 100:(1-5):(1-10):(1-10):(5-20).
3. The alumina-based adsorption material according to claim 1, characterized in that: The organic ligand is triethylenediamine or triethylenetriamine.
4. The alumina-based adsorption material according to claim 1, characterized in that: The organic solvent is tetrahydrofuran or acetone.
5. The alumina-based adsorption material according to claim 1, characterized in that: The mass concentration of the ethanolamine solution is 2-10%, and the mass concentration of the oxalic acid solution is 1-10%.
6. A method for preparing an alumina-based adsorption material according to any one of claims 1 to 5, characterized in that: It includes the following steps: Preparation of precursor: Alternately add ethanolamine solution and oxalic acid solution to sodium aluminate solution to react to obtain colloidal material, and then wash, dry, grind and calcine to obtain the precursor; Preparation of adsorption material: Precursor, metal salt, organic ligand, organic solvent and water are taken, mixed and sealed in a container, then heated to react to obtain a mother liquor, and then the mother liquor is evaporated and dried to obtain a finished adsorption material.
7. The method for preparing an alumina-based adsorption material according to claim 6, characterized in that: In the precursor preparation step, during the process of alternately adding ethanolamine solution and oxalic acid solution, the pH of the system is adjusted to 9.0 when the ethanolamine solution is first added, and the pH of the system is adjusted to 6.0 when the oxalic acid solution is first added; diethanolamine and oxalic acid are alternately added 3 to 5 times, and the pH of the system is finally controlled to 7.
0.
8. The method for preparing an alumina-based adsorption material according to claim 6, characterized in that: In the precursor preparation step, the gelling reaction temperature is 25-40°C.
9. The method for preparing an alumina-based adsorption material according to claim 6, characterized in that: In the adsorption material preparation step, the reaction is heated at 40-60° C. for 12-48 hours to obtain a mother liquid; and the mother liquid is evaporated and dried at 100-180° C. to obtain the adsorption material.
10. Use of the alumina-based adsorption material according to any one of claims 1 to 5 in capturing and purifying carbon dioxide.
Citation Information
Patent Citations
Metal-containing MOR-type zeolite for carbon dioxide capture from
CN118510598A
Preparation method and application of rare earth yttrium-doped alumina nano-material
CN105056876A
Preparation method of alumina solid catalyst carrier
CN115724450A
Preparation method and application of bimetallic MOF adsorption composite material
CN117680112A
Radiation-resistant Al2O3 and MOFs composite aerogel as well as preparation method and application thereof
CN118846975A